Formulation Face Soap Essential Oil StocksBasil (Ocimum Basilicum L.) With CombinedSodium Lauryl Sulfate And Glycerin And TestAntibacterials Of Staphylococcus Epidermidis - Ichsani, Nissa Nur; , Dr. T.N. Saifullah S., M.Si., Apt; , Ratna Yuliani, M. Biotech. St (2016)
Basil essential oil containing linalool has antibacterial activity against Staphylococcus epidermidis which cause acne. Essential oil can be formulated to facilitate its use as anti- acne, one of the dosage form is facial soap. This study aimed to determine the physical properties, stability, and the antibacterial activity of facial soap containing basil oil. Facial soaps contain 12,5% v/v basil essential oil were made in four formulas with concentrations of sodium lauryl sulfate (SLS) and glycerin of 20% (F1), 25% (F2), 30% (F3), and 35% (F4). Facial soap were tested for physical properties and physical stability for 3 months includes organoleptic, viscosity, dispersive capability, foam height, pH, globules size, freeze-thaw test for 6 cycles, and antibacterial activity with diffusion method. Data were analyze using Kruskal-Wallis test and one way ANOVA. Results of physical properties test of facial soap showed a significant increase in viscosity and significant reduction in the dispersive capability, but not significant in the foam height. Stability test of facial soap showed a significant increase in the dispersive capability of F2 and F4, but not significant in F1 and F3, as well as a significant increase in the globules size on freeze-thaw test. The viscosity decreased not significantly in three months storage and freeze-thaw test. Foam height and globule size increase were not significant. Antibacterial activity of facial soap decreased not significantly in three months storage.